Circulating selenoprotein P levels in relation to MRI‐derived body fat volumes, liver fat content, and metabolic disorders. Issue 6 (5th May 2017) - di Giuseppe, Romina; Koch, Manja; Schlesinger, Sabrina; Borggrefe, Jan; Both, Marcus; Müller, Hans‐Peter; Kassubek, Jan; Jacobs, Gunnar; Nöthlings, Ute; Lieb, Wolfgang
Abstract : Objective: Association studies of selenoprotein P (SELENOP) with cardiometabolic traits in humans are relatively scarce and, in part, conflicting. A general population sample from Northern Germany was evaluated for cross‐sectional associations of circulating SELENOP concentrations with metabolic syndrome (MetS), total volumes of MRI‐determined visceral (VAT) and subcutaneous (SAT) abdominal adipose tissue, liver signal intensity, and fatty liver disease (FLD). Methods: Nine hundred and five participants received comprehensive clinical and molecular phenotyping along with measurement of serum SELENOP; 584 individuals received MRI. Results: Multivariable‐adjusted restricted cubic regression splines displayed statistically significant inverse relations of SELENOP levels with MetS, VAT, and SAT ( P < 0.0001 for all). Compared with the second quartile of SELENOP distribution, the MetS odds ratios for the first, third, and fourth quartiles were 1.62 (95% confidence interval [CI]: 1.08‐2.43), 0.85 (95% CI: 0.57‐1.26), and 0.41 (95% CI: 0.27‐0.62), respectively. Furthermore, participants in the second, third, and fourth SELENOP quartiles had significantly lower VAT and SAT volumes as compared to those in the first biomarker quartile. A J‐shaped relation was observed for SELENOP levels and liver signal intensity/FLD ( P = 0.01). Conclusions: The findings suggest inverse associations of circulating SELENOP concentrations with several metabolic traits, to be further investigated in longitudinal studies.